Pengaruh Full Day School Pada Pola Permainan Anak - MUHAMMAD, JAISYU; AL MUBAROK, MUHAMMAD GHOZI; ABDURRAHMAN, IDAM YUSUF; AL FARUQ, HIKAM (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
Abstract This study aims to analyze the influence of the Full Day School system on children's play patterns. With the increasing implementation of the Full Day School education system, children are experiencing drastic changes in their playtime and social interactions with parents, neighbors and the rest of the community. This research uses the literature study method, collecting data from various sources, including books, papers, articles, journals and previous research. The results show that although the Full Day School system can improve learning concentration and supervision of students, there is a negative impact in the form of reduced play time outside of school, which has the potential to hinder the development of children's social and emotional skills. Traditional games that were previously an important part of children's lives are now replaced with modern games or what are commonly called online games just to refresh for a moment. With the full day school system that drains time in children's learning, children are now unable to do activities outside of school, thus reducing children's opportunities to interact directly with their environment. This study concludes that although Full Day School has benefits in affective, cognitive, and psychomotor aspects, it is important for education experts and parents to consider the balance between learning time and play time to support children's development.